Potensi Antidiare dan Profil Fitokimia Ekstrak Elaeocarpus longifolius (Jambu Wer) dengan Perbedaan Pelarut - Bhagawan, Weka Sidha; Maritha, Vevi; Zatalini, Dioni; Mandalawati, Titin; Prasetyo, Yona; Peria, Jo; Santos, Gema; Rivera, Alice; Hison, Jade; Donato, Percival; Amaranto, Jennifer; Tanghal, Analiza; Bhagawan, Weka (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2025)
The ethnopharmacological significance of Elaeocarpus longifolius (Jambu Wer), an indigenous medicinal plant of the Tengger Tribe, remains underexplored. This study evaluates the antibacterial and phytochemical properties of E. longifolius fruit extracts using ethanol, n-hexane, ethyl acetate, and chloroform as solvents. Antibacterial activity was assessed against Escherichia coli and Shigella dysenteriae, pathogens commonly associated with severe diarrhea, using the agar disk-diffusion method. Phytochemical screening was conducted using reagent-based tests and thin-layer chromatography (TLC). The ethanol extract exhibited the highest antibacterial activity, with inhibition zones exceeding 20 mm against both bacterial species. Phytochemical analysis revealed the presence of alkaloids, flavonoids, and tannins (compounds known for their pharmacological properties). These findings highlight the potential of E. longifolius ethanol extract as a promising natural therapeutic candidate for the development of Fitofarmaka targeting diarrheal diseases.